An Analysis of Cost of Attending Medical Education in Nepal - Pokhrel, Rajendra Kumar (Economic Journal of Nepal, 2021)
The purpose of this paper is to investigate cost of attending medical education (MBBS) in Nepal provided by twenty public and private medical colleges affiliated to Tribhuvan University (TU) and Kathmandu University (KU) along with BP Koirala Institute of Health Science (BPKIHS) and Patan Academy of Health Science (PAHS). The basic objectives of the paper are to analyze the costs of attendance (CoA) and its determinants of MBBS education in public and private colleges of Nepal, Primary cost survey upon twenty medical colleges was utilized to gather the cost related data. Four admission cycles (2015-2018) of MBBS students were used for the study. It further revealed differential cost of attendance within universities and within public and private medical colleges. Cost of attendance varies from NRs. 4.3 to 6.1 million and it grew minimum 2.02 percent to maximum 6.4 percent. MBBS education in private medical colleges in Nepal is more expensive than public colleges. It should be made affordable, accessible and reformed on the basis of basic principle of quality health care and health education.